Memorix anatomy : entire human anatomy in English and Latin - Hudák, Radovan; Kachlík, David, 1974-; Volný, Ondřej, 1986- (Triton, 2017)
Přehledná, systematická a stručná učebnice anatomie pro vysokoškolské studenty.
Keywords: anatomie člověka; human anatomy; učebnice; textbooks